Self-perception of research skills: Psychology students in a virtual practice - López-Alonso, Verónica Elsa (2024)
Introduction: Previous research has shown deficiencies in the training of researchers. Objective: To evaluate the perception of the research skills of psychology students belonging to the Research Field from the Behavioral, Cognitive Behavioral and Inter behavioral traditions, and compare it with their level of knowledge about the research process. Method: Eighty-two Psychology students participated in the first application and 70 in the second. A questionnaire was developed to self-assess the perception of research skills and general knowledge of methodology, statistics, and research report writing. Results: The students’ perception was that their investigative skills improved after completing an internship at a distance. Discussion: Inserting students into research groups enhances the development of their research skills, even in a remote model. Some factors involved and the benefits of real situations as a teaching strategy are discussed.